(untitled) (International Journal of Natural Sciences Research, 2015)
Malay apple fruits are susceptible to bruising and degradation with short shelf life. The Malay apple fruit can be economically converted into functional food and consumed as wine. Overcoming challenges of competitive market quality standards and consumer approval must be achieved by producing wines with optimal sensory and physicochemical characteristics during fermentation. The objective was to identify optimal pectolase enzyme concentration that produce, the most superior physicochemical characteristics and consumer acceptability during fermentation. Malay apple wine was made after secondary fermentations of 21 days of ripe fruits using 4 labeled treatments (T1 –T4) different pectolase concentrations 0.0%, 0.3%, 0.6%, 0.9% respectively and the physicochemical characteristics of the treatments were measured. Hedonic testing, focus group evaluation, quality appraisal of the wines and microbiological stability tests were performed. All results were computed statistically using the MINITAB Statistical Software Package. Acidity, Flavor, Finish, Hue, Chroma and Turbidity were superior in theT2 treatments while the T4 treatment scored higher in Aroma and Bouquet, Balance, Body, Overall Acceptability and Alcohol Content. All treatments T1 – T4 were microbiologically stable and contained < 10 cfu.mL-1 of total aerobes, yeast, molds and lactic acid bacteria and were microbiologically stable. It was concluded that treatments T2 and T4 (0.3% and 0.9%) produced dry wines, with the best physicochemical and hedonistic characteristics of the Malay apple wine.